The Roles of Autophagy in Acute Lung Injury Induced by Myocardial Ischemia Reperfusion in Diabetic Rats - Liying Zhan; Yuan Zhang; Wating Su; Qiongxia Zhang; Rong Chen; Bo Zhao; Wei Li; Rui Xue; Zhongyuan Xia; Shaoqing Lei (Journal of Diabetes Research)
Patients with diabetes are vulnerable to myocardial ischemia reperfusion (IR) injury, which may also induce acute lung injury (ALI) due to overaccumulation of reactive oxygen species (ROS) and inflammation cytokine in circulation. Despite autophagy plays a significant role in diabetes and pulmonary IR injury, the role of autophagy in ALI secondary to myocardial IR in diabetes remains largely elusive. We aimed to investigate pulmonary autophagy status and its roles in oxidative stress and inflammation reaction in lung tissues from diabetic rats subjected to myocardial IR. Control or diabetic rats were either treated with or without autophagy inducer rapamycin (Rap) or autophagy inhibitor 3-methyladenine (3-MA) before myocardial IR, which was achieved by occluding the left anterior descending coronary artery for 30 min and followed by reperfusion for 120 min. Diabetic rats subjected to myocardial IR showed more serious ALI with higher lung injury score and WET/DRY ratio and lower PaO2 as compared with control rats, accompanied with impaired autophagy indicated by reduced LC-3II/LC-3I ratio and Beclin-1 expression, decreased superoxide dismutase (SOD) activity, and increased 15-F2t-Isoprostane formation in lung tissues, as well as increased levels of leukocyte count and proinflammatory cytokines in BAL fluid. Improving autophagy with Rap significantly attenuated all these changes, but the autophagy inhibitor 3-MA exhibited adverse or opposite effects as Rap. In conclusion, diabetic lungs are more vulnerable to myocardial IR, which are involved in impaired autophagy. Improving autophagy could attenuate ALI induced by myocardial IR in diabetic rats, possibly through inhibiting inflammatory reaction and oxidative stress.